Generation of an induced pluripotent stem cell (iPSC) line (INNDSUi009-A) from a patient with amyotrophic lateral sclerosis due to SOD1 mutation - Bo Li; Haoran Mu; Didi Shan; Yitong Yang; Yingxin Wang; Jianing Li; Hongxu Wang; Xiaohan Sun; Xinbo Ji; Zexin Zhan; Yichang Jiao; Yao Tang; et al. (Stem Cell Research)
Amyotrophic lateral sclerosis (ALS) is a fatal neurological disorder characterized by progressive degeneration of nerve cells in the spinal cord and brain. We generated and characterized a human induced pluripotent stem cell (iPSC) line from skin fibroblasts of a patient with ALS due to SOD1 Mutation. The pluripotency of these iPSCs was verified by the expression of several pluripotency markers at both RNA and protein levels, as well as their capability to differentiate into all three germ layers.